PENGARUH PERIKLANAN TERHADAP KUNJUNGAN WISATAWAN PADA DESTINASI WISATA LADANG BUDAYA TENGGARONG - Yasintha Eka Rimbawati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
Tourism marketing is one of the most important activities for the order market a product. Every company will do marketing with different ways and cconcepts to attract people’s attention. Advertising becomes one of the important promotion methods for PT. Wahana Ladang Budaya to increase tourist visits. The purpose of this study is to analyze whether promosi (X) affect the level of kunjungan wisatawan (Y) on Ladang Budaya Tenggarong attractions. This type research is quantitative research. Data in obtain sourced from people who visit Ladang Budaya Tengarong attractions by taking a sample of 100 people and the data obtained is sourced from the manager of the Ladang Budaya Tenggarong attractions, with data collection techniques, namely literature study and field studies consisting of questionnaire techniques that have been tested for validity and its reliability. This research method uses simple linear regression analysis method. The results of data processing showed that the results of the regression equation were not experiencing data abnormalities or can be said to be normal data. Results statistical testing shows that the promosi variable has a positive effect to the level of kunjungan wisatawan. T test results indicate that the promosi variable (X) Partially significant effect on the level of kunjungan wisatawan to revisiting the tourism object of the Ladang Budaya Tenggarong. Sugesstions to the manager of the Ladang Budaya Tenggarong is that can continue to improve existing promotions, so that the community can be more get to know more and can follow the latest news about Ladang Budaya attractions.